Analisis Penyusunan Anggaran Penjualan Pada CV Senapan123.com di Kabupaten Kediri - Nuril Aini; Trisnia Widuri; Kukuh Harianto (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to determine the forecasting of air rifle sales at CV Senapan123.com, Kediri Regency. The problem in this research is how to prepare the sales budget at CV Senapan123.com Kediri Regency so that the company is able to manage profits absolutely and can be used as an illustration of sales in the coming year. This research uses quantitative descriptive research. The data sources that researchers use are primary data and secondary data. Primary data is in the form of interviews with the owner of CV Senapan123.com. Secondary data is in the form of air rifle sales data for 2022. The data collection techniques used by researchers are documentation, interviews and literature studies. In sales forecasting, researchers use statistical methods of trend analysis, namely using the trend moment method and the least squares method. From the results of the analysis that has been carried out, it shows that forecasting sales at CV Shotgun123.com in 2023 using the least squares method has increased by 38% with a total of 697 units compared to the previous year. Meanwhile, sales estimates for 2023 using the trend moment method have increased by 106% with a total of 1041 units compared to the previous year.